Religious Art in the Viewpoint of Ayatollah Javadi Amoli - حمید رضا خادمی; Seyed msoud Masoudian (حکمت اسرا)
Ayatollah Javadi Amoli is one of the contemporary thinkers of Islamic world who pays attention to Religious Art and explains its characteristics and principles. Not only does this paper express the definition and the interpretation of Religious Art in his thinking system, but also its characteristics affected by original viewpoints of Transcendent Philosophy. For Ayatollah Javadi Amoli, the most important characteristics of Religious Art are: the supreme place of intellect and intellectual world as the origins of artwork, the role of imagination as the faculty of creating artwork, the importance of the ethical policies of art and artist as well as the cognitive functions and features of art. Given the two elements of motivation and thought in human being, he considers the illustrating world as the policy of Religious Art and the output of process of creating artwork by the projection of Mimesis as the invariable act of Religious Art.